Life in the soil a guide for naturalists and gardeners - Nardi, James B., 1948- (University of Chicago Press, 2007)
Leonardo da Vinci once mused that "we know more about the movement of celestial bodies than about the soil underfoot," an observation that is as apt today as it was five hundred years ago. The biological world under our toes is often unexplored and unappreciated, yet it teems with life. In one square meter of earth, there lives trillions of bacteria, millions of nematodes, hundreds of thousands of mites, thousands of insects and worms, and hundreds of snails and slugs. But because of their location and size, many of these creatures are as unfamiliar and bizarre to us as anything found at the bottom of the ocean. Lavishly illustrated with nearly three hundred color illustrations and masterfully-rendered black and white drawings throughout, Life in the Soil invites naturalists and gardeners alike to dig in and discover the diverse community of creatures living in the dirt below us. Biologist and acclaimed natural history artist James B. Nardi begins with an introduction to soil ecosystems, revealing the unseen labors of underground organisms maintaining the rich fertility of the earth as they recycle nutrients between the living and mineral worlds. He then introduces readers to a dazzling array of creatures: wolf spiders with glowing red eyes, snails with 120 rows of teeth, and 10,000-year-old fungi, among others. Organized by taxon, Life in the Soil covers everything from slime molds and roundworms to woodlice and dung beetles, as well as vertebrates from salamanders to shrews. The book ultimately explores the crucial role of soil ecosystems in conserving the worlds above and below ground.